CATATAN BARU LOKASI DAN INANG UNTUK Cervonemella rear doni BEVERIDGE, 2001 DAN Cloac ina spp . DI INDONESIA - Kartika Dewi; Yuni Apriyanti; Nanang Supriyatna (Widyariset, 2010)
Papua and offshore islands have rich in fauna diversity. Four Cloacininae nematodes have joint been reported from Salawati Island, a small island nearby Papua, i. e. Cervonemella reardoni Beveridge, 2001, Cloacina syphax Beveridge & Speare, 1999, Cloacina polymela Beveridge, 2002 and Cloacina procris Beveridge, 2002. They are from Dorcopsis muelleri (Schlegel, 1866). Herein, those nematodes are also reported with descriptions and illustrations.